Alikoto: Mathematics instruction and cultural games in Ghana - Patrick Owusu; Akosua Obuo Addo (Cogent Education, 2023)
AbstractMeaningful learning occurs when individuals connect their existing knowledge with their current understanding. Unfortunately, many teaching practices neglect the learners' subconscious knowledge, also known as their ”funds of knowledge.” The result is a disconnect between school and home knowledge, social injustice towards students whose parents lack formal education, and frustration among learners.In this paper, we argue that mathematical concepts found in cultural games can teach children in grades 4-6 mathematics in Ghana. By describing math-rich games from Ghanaian culture and showing where they fit into the curriculum, we aim to provide teachers with examples of incorporating cultural games into their instruction. Our project emphasizes the importance of using games to enhance teacher pedagogy by blending established teaching methods with innovative strategies incorporating artistic games.